How to get published in the best political science and international relations journals : understanding the publishing game - Breuning, Marijke (Lowe's how-to series., 2021)
"Providing an insightful and comprehensive introduction to the world of journal publishing within the fields of political science and international relations, this book offers in-depth guidance to maximize the likelihood of publishing success. Using their extensive experience as journal editors, Marijke Breuning and John Ishiyama also include crucial advice on how to select an appropriate journal, revise manuscripts, and how to increase the impact of published work. Common questions are answered, such as: when is the right time to submit your manuscript; how to select a co-author; and when to contact an editor, as well as the challenging aspect of how to deal with rejections. Other key topics are thoroughly reviewed and explored, including guidance on ethics and integrity in publishing journal articles, emerging practices regarding research transparency, and new frontiers in academic journal publishing such as Open Access. This engaging book will be an invaluable resource for graduate students and scholars looking to improve their understanding of the journal publishing process, as well as providing an essential guide for those undertaking this journey for the first time"--